Potentiation of amygdala AMPA receptor activity selectively promotes escalated alcohol self‐administration in a CaMKII‐dependent manner. (6th January 2016) - Cannady, Reginald; Fisher, Kristen R.; Graham, Caitlin; Crayle, Jesse; Besheer, Joyce; Hodge, Clyde W.
Abstract: Growing evidence indicates that drugs of abuse gain control over the individual by usurping glutamate‐linked mechanisms of neuroplasticity in reward‐related brain regions. Accordingly, we have shown that glutamate α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid receptor (AMPAR) activity in the amygdala is required for the positive reinforcing effects of alcohol, which underlie the initial stages of addiction. It is unknown, however, if enhanced AMPAR activity in the amygdala facilitates alcohol self‐administration, which is a kernel premise of glutamate hypotheses of addiction. Here, we show that low‐dose alcohol (0.6 g/kg/30 minutes) self‐administration increases phosphorylation (activation) of AMPAR subtype GluA1 S831 (pGluA1 S831) in the central amygdala (CeA), basolateral amygdala and nucleus accumbens core (AcbC) of selectively bred alcohol‐preferring P‐rats as compared with behavior‐matched (non‐drug) sucrose controls. The functional role of enhanced AMPAR activity was assessed via site‐specific infusion of the AMPAR positive modulator, aniracetam, in the CeA and AcbC prior to alcohol self‐administration. Intra‐CeA aniracetam increased alcohol‐reinforced but not sucrose‐reinforced responding and was ineffective following intra‐AcbC infusion. Because GluA1 S831 is a Ca2+/calmodulin‐dependent protein kinase II (CaMKII) substrate, we sought to determine if AMPAR regulation of enhanced alcohol self‐administration is dependent on CaMKII activity. Intra‐CeA infusion of the cell‐permeable CaMKII peptide inhibitor myristolated autocamtide‐2‐related inhibitory peptide (m‐AIP) dose‐dependently reduced alcohol self‐administration. A subthreshold dose of m‐AIP also blocked the aniracetam‐induced escalation of alcohol self‐administration, demonstrating that AMPAR‐mediated potentiation of alcohol reinforcement requires CaMKII activity in the amygdala. Enhanced activity of plasticity‐linked AMPAR‐CaMKII signaling in the amygdala may promote escalated alcohol use via increased positive reinforcement during the initial stages of addiction. Abstract : Growing evidence indicates that drugs of abuse gain control over the individual by usurping glutamate‐linked mechanisms of neuroplasticity in reward‐related brain regions. Here, we show that low‐dose alcohol self‐administration increases phosphorylation (activation) of AMPAR subtype GluA1 S831 in rat central amygdala and that CaMKII‐dependent activation of AMPA receptors in the amygdala increases the positive reinforcing effects of alcohol. Enhanced activity of plasticity‐linked AMPAR‐CaMKII signaling may promote escalated alcohol use via increased positive reinforcement during the initial stages of addiction.